The onus of cannabinoids in interrupting the molecular odyssey of breast cancer: A critical perspective on UPRER and beyond - Safikur Rahman; Ayyagari Archana; Durgashree Dutta; Vijay Kumar; Jihoe Kim; Arif Tasleem Jan; Rinki Minakshi (Elsevier, 2019)
Cannabinoids, commonly used for medicinal and recreational purposes, consist of various complex hydrophobic molecules obtained from Cannabis sativa L. Acting as an inhibitory molecule; they have been investigated for their antineoplastic effect in various breast tumor models. Lately, it was found that cannabinoid treatment not only stimulates autophagy-mediated apoptotic death of tumor cells through unfolded protein response (UPRER) activated downstream effectors, but also imposes cell cycle arrest. The exploitation of UPRER tumors as such is believed to be a major molecular event and is therefore employed in understanding the development and progression of breast tumor. Simultaneously, the data on clinical trials following administration of cannabinoid is currently being explored to find its role not only in palliation but also in the treatment of breast cancer. The present study summarizes new achievements in understanding the extent of therapeutic progress and highlights recent developments in cannabinoid biology towards achieving a better cure of breast cancer through the exploitation of different cannabinoids. Keywords: Cannabinoids, Unfolded Protein Response (UPR), Endoplasmic reticulum (ER), Breast cancer